Speech Acts: Force Behind Words - Hidayat, Agus (English Education: Jurnal Tadris Bahasa Inggris, 2016)
Speech act is a part of pragmatics where there are certain aims beyond the words or phrases when a speaker says something. Speech acts are acts that refer to the action performed by produced utterances. People can perform an action by saying something. Through speech acts, the speaker can convey physical action merely through words and phrases. The conveyed utterances are paramount to the actions performed. In regard to the English as a foreign language, there are things to consider. It is easy for the speakers or listeners to determine the intended meaning of utterances if they are spoken in the mother tongue. Factors such as idiomatic expressions and cultural norms are not function as barriers to determine the intended meaning.